THE MEDIATING ROLE OF DEBT AND DIVIDEND POLICY ON THE EFFECT PROFITABILITY TOWARD STOCK PRICE - Akhmadi Akhmadi; Nurohman Nurohman; Robiyanto Robiyanto (Jurnal Manajemen dan Kewirausahaan, 2021)
This study aimed to obtain an empirical explanation of the role of debt policy and dividend policy as variables mediating the influence of profitability on stock prices. This study used six mining companies listed on the Indonesia Stock Exchange (IDX) during the period of 2012–2016 as samples, hence there were 30 observational data. The sampling technique in this study was purposive sampling. This study found that profitability had a positive effect on stock prices, but the increasing profitability would not necessarily reduce the debt policy. The increasing profitability did not significantly increase the dividend policy, however, increasing dividend policy would increase the stock prices. The results also proved that debt and dividend policy did not mediate the influence of return on equity on the stock prices.